Glucómetro inductivo: Estudio de viabilidad in vivo - González, C. A.; Campos., J. M.; Polo., S. M.; Martínez., S. G. (Revista Mexicana de Ingenieria Biomedica, 2009)
New technologies focused on the continous and noninvasive glucose monitoring in blood represent non-specificity and poor sensitivity challenges. In this work the design of a noninvasive glucometer which principle is based on the induction of multi-frequency magnetic fields is described. The objectve was to evaluate in vivo the viability to use inductive phase and gain shift measurements as indicators of the glucose concentration level in biological tissue. An experimental inductive spectrometer was designed and teted for the noninvasive monitoring of glycemia in the tail of Wistar rats. Two experimental groups were studied: control and diabetic (hyperglycemia induced). In both experimental groups direct measurements of the glucose concentration in blood as well as inductive phase and gain shifts spectra (0.001 to 50 MHz) were made through a commercial glucometer and the proposed inductive spectrometer respectively. The viability study compares the data getting trough both measurement systems. The results indicate that the evaluate biophysical concept has technical viability to the noninvasive monitoring of glycemia and suggest future sensitivity and specificity studies at low frequencies.